Algorithms "don't see the world the same way we do". Issue 5 (4th October 2018) - Tarran, Brian
Abstract : Mathematician Hannah Fry explores the good, the bad and the ugly of the new machine age Abstract : Mathematician Hannah Fry explores the good, the bad and the ugly of the new machine age, and Google builds a dedicated search tool for data sets.